Adaptive Public Service Management in a Growing Tourism Corridor: Evidence from Ciwidey–Rancabali - Nanang Suparman (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
This study examines the capacity of public service management in the Ciwidey–Rancabali tourism corridor in responding to increasing tourist visits. The urgency arises from the growth of destinations, accommodation facilities, and seasonal tourist mobility, which creates pressure on access, sanitation, safety, information, and institutional coordination. Drawing on New Public Service, Tourism Destination Governance, and Service Quality, this research positions tourism areas as public service spaces requiring adaptive and integrated governance. A qualitative case study design was applied through document study, non-participant observation, and semi-structured interviews with actors involved in tourism service management. The findings show that public service capacity remains uneven because mobility management, basic service quality, complaint handling, and risk mitigation have not fully operated as a corridor-wide service system. The discussion indicates that tourism growth must be evaluated not only through attraction development, but also through institutional ability to ensure comfort, safety, service reliability, and visitor trust sustainably.